Editorial for the Special Issue “Information Technologies in Education, Research, and Innovation” - Eric C. K. Cheng; Tianchong Wang (Information, 2024)
The COVID-19 pandemic has accelerated the integration of education and technology, ushering in a new era where digital tools and innovative approaches take center stage across higher education and beyond [...]